2020
DOI: 10.3389/fchem.2020.00825
|View full text |Cite
|
Sign up to set email alerts
|

Radical Molecular Modulator for High-Performance Perovskite Solar Cells

Abstract: The long-term stability of perovskite solar cells (PSCs) remains an issue impeding their commercialization. Generally, polycrystalline perovskite thin films have many defects on the grain boundaries, which affect the optoelectronic performance and stability of the devices under moisture, heat, illumination, and the presence of an electric field condition. The O-donor Lewis base is often employed to regulate the performance of PSCs such as carbonyl and carboxyl compounds. Herein, we have developed a concept of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This bond was shifted to ∼1650 cm –1 after adding BP into perovskite, which indicates the coordination interaction between BP and Pb 2+ . , Additionally, an absorption peak at 1712 cm –1 is assigned for the stretch vibration of the CN bond in the FA + cation. The CN peak is shifted toward higher wavenumber at ∼1726 cm –1 which is another representation of the interaction between FA + cation in perovskite and the CO bond in BP …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This bond was shifted to ∼1650 cm –1 after adding BP into perovskite, which indicates the coordination interaction between BP and Pb 2+ . , Additionally, an absorption peak at 1712 cm –1 is assigned for the stretch vibration of the CN bond in the FA + cation. The CN peak is shifted toward higher wavenumber at ∼1726 cm –1 which is another representation of the interaction between FA + cation in perovskite and the CO bond in BP …”
Section: Resultsmentioning
confidence: 95%
“…The C�N peak is shifted toward higher wavenumber at ∼1726 cm −1 which is another representation of the interaction between FA + cation in perovskite and the C�O bond in BP. 40 The mechanism of the interaction between BP and FAPbI 3 is shown in Figure 5b. Two mechanisms of bonding between BP and FAPbI 3 are possible based on FTIR spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 3(b). showed that emission wavelength around 770 nm with a grander intensity for 1-Pentanethiol incorporated perovskite layers, signifying suppressed non-radiative recombination and thus responsible defects and trap-states [26,38,[58][59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…Triphenylamine derivatives are one of the materials most frequently used as hole-transporting layers. ,, TEMPO cations have been mixed with triphenylamines as oxidants (Figure ). The oxygen-scavenging properties of radical polymers helped to protect perovskite layers from degradation by oxygen. …”
Section: Application Of Organic Radicals In Energy Conversion/storage...mentioning
confidence: 99%